Respiratory symptoms and pulmonary function among male steel workers in Terengganu, Malaysia - Hamzah, Nurul Ainun; Mohd Tamrin, Shamsul Bahri; Ismail, Noor Hassim (Malaysian Public Health Physicians’ Association, 2014)
A cross sectional study was carried out to determine the relationship between dust exposure and pulmonary function in male steel workers in Terengganu, Malaysia. The investigation included spirometric testing and detailed personal interviews using a structured questionnaire adopted from British Medical Research Council (BRMC) Questionnaire on respiratory symptoms. Respiratory symptoms commonly reported by the male workers were morning phlegm (33.1%), shortness of breath (31.9%), chest tightness (30.4%), and morning cough (17.8%). Age and duration of employment were among the factors associated with respiratory symptoms (p<0.05 and p<0.001 respectively). Forced Expiratory Volume in 1 second (FEV1) was significantly reduced when compared to the healthy population. There was a significant decrease of FEV1 between before and after work shift (t= 3.582, p<0.001). Smoking status, age, and duration of employment were also associated with reduction of pulmonary function (p<0.01).